Estudio Restrospectivo del Distemper Canino en la zona 5 - Aldas Cárdenas, Nancy Guadalupe (2017)
In the Provinces belonging to Zone 5 (Bolívar, Los Ríos, Guayas and Santa Elena), the presence of Distemper Canino was evaluated; The descriptive qualitative statistical model was applied, in a total of 1505 clinical records. Percentages, means, frequency and graphs were determined. The objectives were: 1) To determine the incidence of Canine Distemper in zone 5. 2) To establish the characteristics of Canine Distemper in each province. 3) Determine in which period of life the individual presented the disease. The experimental variables and results were: Prevalence 20%; Origin Provincia Bolívar 59%; Breed Frensh Poodle 33%; Sex 61% male; Age 43% 3rd month; Body condition 65% thin; Weather station 72% summer; Clinical signs 35% overall (anorexia 20%); And Mortality 85%; Finally, this research determined that the retrospective study of Canine Distemper in zone 5 was related by coefficients to the animal's immune status, which are more likely to contract the disease, increasing the risk of infection.